Insights on the impact of COVID-19 and the lockdown on amateur golfers - Huth, C.; Billion, F. (Quality in Sport, 2021)
The aim of the research paper is to evaluate how golfers feel about the lockdown, what they did with regard to golf during the lockdown and to what extent they understand the closure of golf courses. A standardized online questionnaire was designed for the primary empirical investigation. In total, 139 respondents completely filled out the questionnaires and were considered in our analyses. The results show that the officially ordered lockdown did not have a large impact on golfers but had at least a medium-to-increased negative influence on their favourite sport of golf. The closure of the golf courses during the lockdown led to a moderate level of approval. The length of the closure tends to be viewed negatively. Despite the problems that golf can expect in the short term, golf as a health- and well-being-promoting sport and a sport that offers natural experiences could benefit from COVID-19 in the medium to long term.